Théorie des jeux expérimentale & action motrice - Collard, Luc (2011)
How do sportspeople succeed in a non-collaborative game? An illustration of a perverse side effect of altruism Are team sports specialists predisposed to collaboration? The scientific literature on this topic is divided. The present article attempts to end this debate by applying experimental game theory. We constituted three groups of volunteers (all students aged around 20): 25 team sports specialists; 23 individual sports specialists (gymnasts, track & field athletes and swimmers) and a control group of 24 non-sportspeople. Each subgroup was divided into 3 teams that played against each other in turn (and not against teams from other subgroups). The teams played a game based on the well-known Prisoner's Dilemma (Tucker, 1950) - the paradoxical "Bluegill Sunbass Game" (Binmore, 1999) with three Nash equilibria (two suboptimal equilibria with a pure strategy and an optimal equilibrium with a mixed, egotistical strategy (p= 1/2)). This game also features a Harsanyi equilibrium (based on constant compliance with a moral code and altruism by empathy: "do not unto others that which you would not have them do unto you"). How, then, was the game played? Two teams of 8 competed on a handball court. Each team wore a distinctive jersey. The game lasted 15 minutes and the players were allowed to touch the handball ball with their feet or hands. After each goal, each team had to return to its own half of the court. Players were allowed to score in either goal and thus cooperate with their teammates or not, as they saw fit. A goal against the nominally opposing team (a "guardian" strategy, by analogy with the Bluegill Sunbass Game) earned a point for everyone in the team. For an own goal (a "sneaker" strategy), only the scorer earned a point - hence the paradox. If all the members of a team work together to score a goal, everyone is happy (the Harsanyi solution). However, the situation was not balanced in the Nashian sense: each player had a reason to be disloyal to his/her team at the merest opportunity. But if everyone adopts a "sneaker" strategy, the game becomes a free-for-all and the chances of scoring become much slimmer. In a context in which doubt reigns as to the honesty of team members and "legal betrayals", what type of sportsperson will score the most goals? By analogy with the Bluegill Sunbass Game, we recorded direct motor interactions (passes and shots) based on either a "guardian" tactic (i.e. collaboration within the team) or a "sneaker" tactic (shots and passes against the player's designated team). So, was the group of team sports specialist more collaborative than the other two groups? The answer was no. A statistical analysis (difference from chance in a logistic regression) enabled us to draw three conclusions: ?For the team sports specialists, the Nash equilibrium (1950) was stronger than the Harsanyi equilibrium (1977). ?The sporting principles of equilibrium and exclusivity are not appropriate in the Bluegill Sunbass Game and are quickly abandoned by the team sports specialists. The latter are opportunists who focus solely on winning and do well out of it. ?The most altruistic players are the main losers in the Bluegill Sunbass Game: they keep the game alive but contribute to their own defeat. In our experiment, the most altruistic players tended to be the females and the individual sports specialists